2011
DOI: 10.1177/0961203311432740
|View full text |Cite
|
Sign up to set email alerts
|

A case of steroid-resistant nephrotic syndrome associated with systemic lupus erythematosus

Abstract: We report on an 11-year-old girl who developed steroid-resistant nephrotic syndrome (NS) at the onset of systemic lupus erythematosus (SLE), and clinical and renal histological findings suggested that her NS would be associated with SLE-related podocytopathy. Although initial treatment with intravenous pulse methylprednisolone was ineffective, following treatment with cyclosporine and an angiotensin receptor blocker was effective for her nephrotic proteinuria. She had developed posterior reversible encephalopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Additional immunosuppressive agents including CTX, 14 AZA, 9,14 MMF, 3,31,32 cyclosporine (CsA), 12,15 and anti-CD20 monoclonal antibody, 33 as well as double filtration plasmapheresis 23 were reported to be combined with glucocorticoid for inducing remission of lupus podocytopathy. However, all of these publications were case reports and most were indicated in patients who were refractory to glucocorticoid.…”
Section: Discussionmentioning
confidence: 99%
“…Additional immunosuppressive agents including CTX, 14 AZA, 9,14 MMF, 3,31,32 cyclosporine (CsA), 12,15 and anti-CD20 monoclonal antibody, 33 as well as double filtration plasmapheresis 23 were reported to be combined with glucocorticoid for inducing remission of lupus podocytopathy. However, all of these publications were case reports and most were indicated in patients who were refractory to glucocorticoid.…”
Section: Discussionmentioning
confidence: 99%
“…Simple criteria to diagnose lupus podocytopathy are (1) lupus patient with nephrotic syndrome, (2) diffuse and severe foot process effacement and (3) the absence of subendothelial or subepithelial immune deposits [20]. Up till now, the frequency, prognosis and treatment of LP are not well established in p-SLE except for one case report of Ito et al [25] who reported an 11-year lupus girl who developed steroid-resistant nephrotic syndrome (SRNS) at disease onset and her histological findings were consistent with LP. LP represents 8.93% of renal pathology in our patients, which is consistent with other reports [6,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotic syndrome is usually associated with diffuse or membranous. LN [ 9 ]. However, membranous LN or mesangial proliferative LN is rare in children.…”
Section: Discussionmentioning
confidence: 99%